Study of cement pastes rheological behavior using dynamic shear rheometer - Teixeira,J. E. S. L. (2014)
Concrete, in its fresh state, has flow characteristics that are crucial to its proper launch and densification. These characteristics are usually measured through empirical testing as the slump test, but this test does not quantify completely the material behavior. Since this material is characterized as a Bingham fluid, it is essential the study of its rheological behavior to verify its properties even in fresh state. The use of classical rheology has been employed by the scientific community to obtain rheological parameters determinants to characterize this material, such as yield stress, plastic viscosity and evolution of shear stress to shear rate. Thus, this present study aims to determine the rheological behavior of different cement pastes produced with cement CP III 40 RS, varying between them the hydration periods (20 and 60 min), the water-cement ratio (0.40, 0.45 and 0.50) and the use or not of additive. Samples were assayed by flow test to determine the rheological parameters showing the effect of the variables mentioned above in these parameters.